The factors that influence visitor’s purchasing decision tour packages to Pulau Payar Marine Park, Kedah / Nuraini Mardiah Mohamed Nasir, Nur Izzati Alias and Siti Nor Farhana Mohd Said - Mohamed Nasir, Nuraini Mardiah; Alias, Nur Izzati; Mohd Said, Siti Nor Farhana (2015)
This study is designed to identify the factors influence visitor’s purchasing tour packages to Pulau Payar Marine Park (PPMP). Services and price are the independent variables. The dependent variable is visitor purchase decision. The objectives of the study are to identify the most factor influence visitor’s purchase decision tour packages and to identify the relationship between visitor’s motivation and the factors influences visitor purchase decision. The data set in this study are collected from the visitors using tour packages in PPMP through questionnaires. A number of 108 respondents in that area had become the sample in this study by answering the questionnaires that randomly distributed.